Mechanism and Treatment Related to Oxidative Stress in Neonatal Hypoxic-Ischemic Encephalopathy - Qin, Xingping; Cheng, Jing; Zhong, Yi; Mahgoub, Omer Kamal; Akter, Farhana; Fan, Yanqin; Aldughaim, Mohammed; Xie, Qiurong; Qin, Lingxia; Gu, Lijuan; Jian, Zhihong; Xiong, Xiaoxing; et al. (Frontiers in Molecular Neuroscience, 2019)
Hypoxic Ischemic Encephalopathy (HIE) is a type of neonatal brain injury, which occurs due to lack of supply and oxygen deprivation to the brain. It is associated with a high morbidity and mortality rate. There are several therapeutic strategies that can be used to improve outcomes in patients with HIE. These include cell therapies such as marrow mesenchymal stem cells (MSCs) and umbilical cord blood stem cells (UCBCs), which are being incorporated into the new protocols for the prevention of ischemic brain damage. The focus of this review is to discuss the mechanism of oxidative stress in HIE and summarize the current available treatments for HIE. We hope that a better understanding of the relationship between oxidative stress and HIE will provide new insights on the potential therapy of this devastating condition.